The role of a community conversation intervention in reducing stigma related to lower limb lymphoedema in Northern Ethiopia - Abebayehu Tora; Stephen Bremner; Oumer Ali; Mersha Kinfe; Asrat Mengiste; Vasso Anagnostopoulou; Abebaw Fekadu; Gail Davey; Maya Semrau (BMC, 2024)
Abstract Background Stigma related to lower-limb lymphoedema poses a major psychosocial burden to affected persons and acts as a barrier to them accessing morbidity management and disability prevention (MMDP) services. Community Conversation (CC), which actively engages community members and disseminates health information amongst them, is believed to break the vicious cycle of stigma by enhancing disease-related health literacy at the community level. Methods A quasi-experimental study was conducted in Northern Ethiopia to assess the role of the CC intervention in reducing stigma. In two control districts, a comprehensive and holistic MMDP care package was implemented that included physical health, mental health and psychosocial interventions, whilst in the intervention district the CC intervention was added to the MMDP care package. A total of 289 persons affected by lymphoedema and 1659 community members without lymphoedema were included in the study. Results Over the course of the intervention, in all sites, community members' knowledge about the causes of lymphoedema increased, and perceived social distance and stigmatizing attitudes towards people with lymphoedema decreased in the community, whilst experienced and internalized stigma decreased amongst affected persons. There were no significant changes for perceived social support. However, the changes were greater in the control sites overall, i.e. those districts in which the holistic care package was implemented without CC. Conclusion The findings suggest that the CC intervention provides no additional stigma reduction when used alongside a holistic MMDP care package. Provision of comprehensive and holistic MMDP services may be adequate and appropriate to tackle stigma related to lower-limb lymphoedema in a resource-constrained setting like Ethiopia.